INCREASING THE EFFICIENCY OF OPERATIONAL MANAGEMENT IN JOINT-STOCK COMPANIES - Ermatov Tokhir Sharipdjanovich (European Science Publishing, 2025)
This article examines the strategic importance of increasing the efficiency of operational management in joint-stock companies, with a focus on enhancing corporate governance, resource optimization, and long-term sustainability. In the context of intensifying market competition and accelerating technological advancement, operational management plays a pivotal role in ensuring the adaptability and resilience of joint-stock companies. The study explores key factors influencing management efficiency, including the implementation of digital tools, restructuring of internal processes, and strengthening of accountability mechanisms within managerial hierarchies. Emphasis is placed on the integration of performance-based evaluation systems and data-driven decision-making to drive productivity and shareholder value. Methodological approaches involve comparative analysis of best practices in corporate governance and empirical data from both developed and emerging markets. The article concludes by proposing a framework for continuous improvement in operational management through innovation, transparency, and stakeholder engagement. These recommendations aim to bolster the competitiveness and financial stability of joint-stock companies in dynamic economic environments.
Keywords: Operational management efficiency; joint-stock companies; corporate governance; resource optimization; sustainability; market competition; technological advancement; digital transformation; internal process restructuring; managerial accountability.